International handbook of structural fire engineering - LaMalva, Kevin; Hopkin, Danny (The Society of Fire Protection Engineers Series (SFPES), 2021)
This Handbook is focused on structural resilience in the event of fire. It serves as a single point of reference for practicing structural and fire protection engineers on the topic of structural fire safety. It is also stands as a key point of reference for university students engaged with structural fire engineering. Maximizes reader understanding of the concepts of structural fire safety and why/how they emerged and evolved over time Discusses what design fire models exist, when they might be chosen and why Details how different materials respond to fire and the methods that can be employed to attempt to ensure adequate structural response in fire Provides guidance concerning how solutions can be adequately implemented during the construction process Reviews the means by which post-fire performance can be interrogated and under what circumstances different structural forms can or cannot be re-instated.